A PROPOSED METHODOLOGY TO EVALUATE SPECIFIC APPLICATIONS OF EXTENDED SURFACES IN INDUSTRIAL EQUIPMENT - Ferreira, A. L. G.; Stampa, C. S.; Lobão, D. C.; Alvarez, G. B. (Revista de Engenharia Térmica, 2020)
The concept of Passive Cooling fits into a number of technological options involving constructive elements, whereby the heat exchange area of a surface being cooled by a surrounding fluid medium occurs. Thus, the increase in area results in an increase in the surface heat dissipation rate for the refrigerant, inferring only a single cost, i.e. the construction cost. Among the available technical possibilities, the use of extended surfaces, known as fins, stands out. The present work focuses on the use of fins on three very common electrical devices in the industrial environment, which present a great need for cooling.They are: three-phase transformer, frequency inverter and induction electric motor. The study is dedicated to a theoretical evaluation of the use of the fin profiles used in these equipments, since the manufacturers do not make their design data available to the public. Thus, a methodology was developed for this evaluation, including comparison of the results between the original profiles of these equipments with an alternative profile of similar design. Within the process of calculating the heat dissipation rates by the fins, the axial temperature distribution profiles were numerically determined using the Finite Difference discretization method, together with the Gauss-Seidel iterative method for the resolution of the discretized equations. The computational code was developed using MatLab® software. The results of the present work attested to the proper use of the original profiles employed by the manufacturers.